A 17-Year Systematic Content Analysis of Social Class and Socioeconomic Status in Two Counseling Journals. (2nd July 2020) - Cook, Jennifer M.; Clark, Madeline; Wojcik, Katharine; Nair, Dhanya; Baillargeon, Tara; Kowalik, Eric
Abstract: We conducted a qualitative, systematic content analysis of articles from 2 counseling journals ( N =  636), Counselor Education and Supervision and Counseling and Values, to understand social class and socioeconomic status (SES) term usage and operationalization. Through PRISMA procedures, electronic text data mining, and consensual coding processes, we found a high number of social class and SES terms ( N =  537) present; however, terms were used infrequently and problematically, including term conflation and term misuse. Additionally, we uncovered high rates of problematic social class and SES term use and variable application (86.67%) in the empirical article subsample. Variable application issues in the empirical subsample were related to data analysis, data collection, data reporting, or term operationalization. Based on the study findings, we offer recommendations to counseling researchers to strengthen their social class and SES terminology usage and variable operationalization and suggest how such strengthening has the capacity to affect counselor education research and counseling practice.